Corrigendum to “Impact of on-hours versus off-hours admission on outcome in pediatric patients with testicular torsion” [American Journal of Emergency Medicine 2025;88:1-6] - Zvizdic, Zlatan (2025)
The authors regret that the acknowledgement to Qatar National Library (QNL) for covering article processing fee was omitted from the final version of the published manuscript. The authors would like to apologise for any inconvenience caused.